Perancangan Mesin Perajang Bawang dengan Model Pemotongan Horisontal Puli Engkol - Riswan Eko Wahyu Susanto; Hiding Cahyono; Ahmad Dzulfikri Halimi; Aditya Sandy Pratama; Moch. Fiky Frediansyah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Community Small and Medium Enterprises (MSMEs) have an important role in advancing the Indonesian economy. One of them is MSME UD. NATURAL FOOD which operates in the field of processing various types of onions. After observations, there are deficiencies in the onion chopping machines currently in use which cannot produce premium grade processed onions. The solution to this problem is to create a Transmission Design and Premium Horizontal Shallot Chopper Blade with an Output Capacity of 15 Kg Per Hour. It is hoped that this tool can help produce quality fried shallots. The method used in design is a design method that begins with observation and literature study, then continues with the planning stage including (planning the transmission system and chopper system). The results obtained in designing this machine show the size of the machine with dimensions of 70 cm wide, 145 cm long, 89 cm high, using 3 mm thick angle iron as part of the frame. And the results of the calculation of the load on the hopper is 231.4 N, the load on the transmission is 138.84 N, the load on the electric motor is 112.14 N. The heaviest load on the frame is on the hooper, amounting to 231.4 N. From the results of the data above it will then be Loading simulations were carried out, the results obtained were stress analysis (yield strength) of 25,000N, maximum displacement analysis on the frame of 5.287mm, and factor of safety analysis on the frame of 5.5. 4 then the frame is declared safe . And it has been designed and made safe to use, because no damage occurs to the frame when the machine is operated. Based on the design results of the transmission and premium horizontal premium onion chopper blade with an output capacity of 15 kg per hour, the engine torque (T) is 545,04 Nm. The engine power requirement is 1,566 kW. The pulley ratio on the machine is (1:10). Pulley diameter 3.8. The shaft diameter is 19 mm and the resulting chopping capacity is 17,4 m^2/hour.